Verwahrung im Jugendstrafrecht – ein Systembruch ohne Vollzugskonzept - Isenhardt, Anna; Marti, Irene; Pruin, Ineke; Richter, Marina; Weber, Jonas (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
The detention of young people poses not only a legal and ethical challenge, but also a practical one. The current amendment to the law marks a fundamental break with the Swiss juvenile criminal justice system, which has traditionally focused on education, protection, and rehabilitation. At present, it is unclear how and where the detention of young people is to be carried out. This article examines the existing structures of detention for adults and provides an insight into life in detention from the perspective of those affected. The authors argue that the social isolation and lack of future prospects associated with detention in a primarily security-oriented environment can increase the psychological stress and risk of recidivism among young detainees. Neuroscientific and developmental psychological findings on brain maturation in young people underscore the problem of indefinite preventive detention in this age group. Finally, the question is raised as to whether a form of detention that complies with human rights is even possible for young people or whether preventive detention represents an unworkable break with the system. (machine translation)